Standardized Uptake Values from PET/MRI in Metastatic Breast Cancer: An Organ‐based Comparison With PET/CT. Issue 3 (4th February 2016) - Pujara, Akshat C.; Raad, Roy A.; Ponzo, Fabio; Wassong, Carolyn; Babb, James S.; Moy, Linda; Melsaether, Amy N.
Abstract: Quantitative standardized uptake values (SUVs) from fluorine‐18 (18F) fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) are commonly used to evaluate the extent of disease and response to treatment in breast cancer patients. Recently, PET/magnetic resonance imaging (MRI) has been shown to qualitatively detect metastases from various primary cancers with similar sensitivity to PET/CT. However, quantitative validation of PET/MRI requires assessing the reliability of SUVs from MR attenuation correction (MRAC) relative to CT attenuation correction (CTAC). The purpose of this retrospective study was to assess the utility of PET/MRI‐derived SUVs in breast cancer patients by testing the hypothesis that SUVs derived from MRAC correlate well with those from CTAC. Between August 2012 and May 2013, 35 breast cancer patients (age 37–78 years, 1 man) underwent clinical 18F‐FDG PET/CT followed by PET/MRI. One hundred seventy metastases were seen in 21 of 35 patients; metastases to bone in 16 patients, to liver in seven patients, and to nonaxillary lymph nodes in eight patients were sufficient for statistical analysis on an organ‐specific per patient basis. SUVs in the most FDG‐avid metastasis per organ per patient from PET/CT and PET/MRI were measured and compared using Pearson's correlations. Correlations between CTAC‐ and MRAC‐derived SUVmax and SUVmean in 31 metastases to bone, liver, and nonaxillary lymph nodes were strong overall (ρ = 0.80, 0.81). SUVmax and SUVmean correlations were also strong on an organ‐specific basis in 16 bone metastases (ρ = 0.76, 0.74), seven liver metastases (ρ = 0.85, 0.83), and eight nonaxillary lymph node metastases (ρ = 0.95, 0.91). These strong organ‐specific correlations between SUVs from PET/CT and PET/MRI in breast cancer metastases support the use of SUVs from PET/MRI for quantitation of 18F‐FDG activity.